Pengaruh Struktur Modal, Likuiditas, Profitabilitas dan Umur Perusahaan terhadap Kualitas Laba: - Khoirunnisa Nur Hasanah; Teguh Erawati (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to prove the effect of capital structure, liquidity, profitability and firm age on earnings quality. The type of research used is quantitative research and secondary data. The sample of this research is mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020 using purposive sampling. This study shows that capital structure has no significant effect on earnings quality, liquidity has no significant effect on earnings quality, profitability has no significant effect on earnings quality and firm age has no significant effect on earnings quality. The implications of this research are related to earnings quality. Investors and other users of financial statement information, need to consider the liquidity factor because this factor has a significant impact on the quality of earnings in the company. This shows that users of financial statements, especially investors, need to consider the liquidity factor when making investment decisions in affiliated companies. Keywords: Capital Structure, Liquidity, Profitability, Company Age, Earnings Quality